IDENTIFYING KEYWORDS ON THE BASIS OF CONTENT MONITORING METHOD IN UKRAINIAN TEXTS - Bisikalo, O. V.; Vysotska, V. A. (Radio Electronics, Computer Science, Control, 2016)
The task of developing algorithmic providing processes of content monitoring for the problem solution of determining a keyword in Ukrainian text is solved. The formal justification of content monitoring in text using Porter stemmer is considered. The basis of the stemming modification is the known results of morpheme and word building structure derivatives classification in Ukrainian language, affix combinatorics patterns identification, modeling the structural organization of verbs and suffixal nouns and morphonological modifications in the verb inflection and word formation and inflection of adjectives in Ukrainian language. The method decomposition is conducted and the algorithmic software of its basic structural components of the text content analysis results is developed. Theoretically means to improve the performance indicators of keywords search are identified, including keyword density in text. Based on the software obtained results of experimental testing of the proposed method of content monitoring to keywords identification in scientific texts of technical profile are developed. It is detected that the chosen experimental base of 100 works the article analysis method the without the initial required information and without the reference list reaches the best results for the density criterion, but with the specified blocked words and qualifying thematic dictionary verification.